Eksplorasi Potensi Pasir Besi di Pesisir Barat Kecamatan Nusawungu Kabupaten Cilacap Berdasarkan Data Resistivitas Batuan Bawah Permukaan: Sukmaji Anom Raharjo, Muhammad Sehah - Sukmaji Anom Raharjo Sukmaji Anom Raharjo; Sehah Sehah (Jurnal Fisika dan Aplikasinya, 2018)
Geophysical exploration to estimate the potency of iron sand in the western coastal area of Sub-district of Nusawungu, Regency Cilacap has been done in May-July 2017 using the resistivity method. Measurements of resistivity data were performed at six points of locations estimated to contain iron ore prospectly based on the local magnetic anomaly map of research area. The geo-electric resistivity survey aims to estimate the depth and thickness of iron sand deposits and their potential. The results of modeling and interpretation of resistivity data show the presence of rock deposit that be estimated as iron sand that coexists alternately with silt and clay from the alluvium formation at all points of locations. The iron sand deposits is at depths of 2.39-25.25 meter with resistivity values of 12.24-46.96 Om. Therefore the resistivity method exploration, shows that the potency of iron sand in the research area is estimated to be quite large.